Which, renewable or non-renewable energy, is more vital for the economic growth of OECD countries? A Bayesian hierarchical analysis - Nguyen Ngoc Thach (Heliyon)
OECD countries have made notable strides in energy transition, but further examination of the interplay between renewables and non-renewables is essential for informed energy policy. Conventional statistical methods face challenges like multicollinearity when exploring the impacts of these energy sources on economic growth. In light of this issue, a Bayesian mixed-effects (hierarchical) regression framework provides a flexible and efficient alternative. This study employs such an approach to dissect the specific contributions of renewables and non-renewables to aggregate output growth in OECD countries. With substantial investments in renewable technologies, it is anticipated that renewables will increasingly contribute to economic growth. Interval hypothesis tests are conducted to scrutinize the data, and the findings validate the expectation that renewables exert a more substantial effect on economic growth in OECD nations. These outcomes provide a robust empirical foundation for shaping energy transition policies.